Efeito antinociceptivo, antidepressivo e ansiolítico dos extratos das partes aéreas de Sonchus oleraceus L. (serralha) - Vilela, Fabiana Cardoso (2009)
Sonchus oleraceus has been used to relieve pain in Brazilian folk medicine and in culinary. Nevertheless, available scientific information regarding this species is scarce; there are no reports related to its possible effect on the central nervous system. This study evaluated the antinociceptive, anxyolitic and antidepressant-like of hydroethanolic and dichloromethane extracts of S. oleraceus .The formalin, hot plate, and tail immersion tests as well as acetic acid-induced writhing were used to investigate the antinociceptive activity in mice. The anxyolitic effect of S. oleraceusi was evaluated n mice submitted to the elevated plus-maze and open-field tests. The putative antidepressant-like effects of extracts was evaluated on the performance of male mice in the forced swimming test (FST) and tail suspension test (TST) models predictive of antidepressive drugs. The extracts at test doses of 30-300 mg/kg, p.o. clearly demonstrated antinociceptive activity in formalin, hot plate, tail immersion and acetic acid-induced writhing tests. The extracts administered at 300 mg/kg, p.o. had a stronger antinociceptive effect than indomethacin (5 mg/kg, p.o.) and morphine (10 mg/kg, p.o.). In the elevated plus-maze test, the S. oleraceus extracts increased the percentage of open arm entries and time spent in the open-arm portions of the maze. The extracts induce an antithigmotactic effect, evidenced by increased locomotor activity into the central part of the open field set-up. The extracts administered at 30- 300 mg/kg, p.o. had a similar anxiolytic effect to clonazepam (0.5 mg/kg, p.o.). The immobility time in both FST and TST was significantly reduced by acute oral treatment with the extracts (dose range 100–300 mg/kg), without accompanying changes in ambulation, as assessed in an open-field test. This excluded the possibility that the effect of the extracts is due to an activation of locomotion. The efficacy of the extracts was found to be comparable to that of amitriptyline (10 mg/kg, p.o.). The extracts of Sonchus oleraceus markedly demonstrated antinociceptive, anxyolitic and antidepressantlike action in mice.